Tiller's guide to Indian country : economic profiles of American Indian reservations - Tiller, Veronica E. Velarde (BowArrow Publishing Company, 2015)
This reference edition profiles each tribe's history and culture, with detailed information about their communities, natural resources, enterprises, and environmental concerns, as well as their contact information.